Development of Canva-Based Sports Learning Media to Enhance Elementary Students' Understanding of Sport Types - Pratama, Kukuh Wahyudin; Purnomo, Sigit; Kartika, Rani; Al-Ihsan, M. Iqbal; Andriani, Dia; Kodri, Suci (Vocational: Journal of Educational Technology, 2025)
The integration of digital media in elementary education is crucial for supporting students’ conceptual understanding, especially in subjects such as physical education, where visual and interactive learning tools can enhance comprehension. This study aims to develop Canva-based sports learning media designed to improve elementary students’ understanding of sport types. The development process followed the 4D model (Define, Design, Develop, and Disseminate), with a sample of 30 fifth-grade students from an elementary school in Yogyakarta, selected through purposive sampling. The media includes interactive and visually engaging content, such as categorized illustrations of ball sports and home-based physical activities, aligned with the national physical education curriculum. Validity testing involved evaluations from subject matter and media experts, resulting in an average validity score of 90.5%, classified as “very valid.” Practicality testing, based on student responses, produced an average score of 89.25%, also categorized as “very practical.” These findings indicate that the developed media is both pedagogically sound and technically feasible for classroom use. The study concludes that Canva-based learning media can serve as an effective instructional tool for enhancing conceptual understanding of sport types in elementary education. It offers a creative, accessible, and engaging alternative to traditional instructional resources, supporting both educators and learners in achieving curriculum goals.